Value for Money: Auditing Public Broadcasting Performance in Sweden - Hultén, Lof (Javnost-The Public, 2003)
The four national broadcasters in Sweden are required by Parliament to present annually self audited public service reports, on how they fulfil their chartered service obligations. Reports have been submitted since 1997. An independent Broadcasting Commission reviews the reports to make sure they meet the needs of the ultimate recipients of the report: the government and the public at large. The purpose of the self-audited performance reports is two-fold: to stimulate public discussion about public service broadcasting and to be useful in the political evaluation of these services. The reports published so far have not led to much public discussion. Its first Parliamentary use will come when a special committee prepares a report to Parliament on the future of public service broadcasting for the next charter period from 2006.